Evaluation of 16S rRNA broad range PCR assay for microbial detection in serum specimens in sepsis patients. Issue 7 (July 2020) - Mishra, Deepanshi; Satpathy, Gita; Wig, Naveet; Fazal, Farhan; Ahmed, Nishat Hussain; Panda, Subrat Kumar
Abstract: Background: Early and accurate laboratory diagnosis and appropriate management of infection improves the survival rate in sepsis. In this study we evaluated broad range 16S rRNA and 16 S–23 S intergenic spacer region (ISR) PCR assays followed by nucleotide sequencing directly from patients' serum and automated blood culture for laboratory diagnosis in admitted sepsis patients. Methods: A broad range 16S rRNA PCR and 16 S–23 S ISR PCR assay followed by nucleotide sequencing was used directly from patients' serum in hospital admitted patients in 62 sepsis and 16 suspected blood stream infection (sBSI) patients. Automated blood culture was also used in the same patients. Nucleotide sequences were analyzed against NCBI Genbank database and organisms were identified using CLSI MM18A guidelines. Results: Bacterial culture were positive in 10/62 (16.12%) sepsis and 3/16 (18.75%) suspected BSI patients along with 3 detected fungi (2 in sepsis and 1 in suspected BSI group). PCR assay was positive in 36/62 (58.06%) sepsis and 6/16 (37.5%) suspected BSI patients respectively. All but 2 bacteria (both from culture negative patients) detected by PCR assay could be identified from nucleotide sequencing. Survival in sepsis patients was 77%. PCR assay could detect bacteria in 9/14 (64.28%) of sepsis patients with death. Conclusion: Broad range PCR assay was far superior for early diagnosis of infection. The bacteria which could not be detected by culture and were not commonly reported from this centre, were detected by the broad range PCR assays. Detection of these rare bacteria/fungi had significant clinical correlation with patient's underlying clinical conditions, immune status and prognosis. The tests could provide definitive diagnosis of infection in >58% of sepsis patients, which helped in patient management and better survival.